Higher HbA1c Measurement Quality Standards are Needed for Follow-Up and Diagnosis: Experience and Analyses from Germany - Heinemann, Lutz; Kaiser, Patricia; Freckmann, Guido; Grote-Koska, Denis; Kerner, Wolfgang; Landgraf, Rüdiger; Merker, Ludwig; Müller, Ulrich A.; Müller-Wieland, Dirk; Roth, Johannes; Spannagl, Michael; Wallaschofski, Henri; Nauck, Matthias (Hormone and Metabolic Research, 2018)
Measurement of HbA1c is an essential laboratory measure for the follow-up and therapy decision-making in patients with diabetes. HbA1c is one of the measurands in laboratory medicine that have to be successfully checked according to the criteria of the guidelines of the German Medical Association (Rili-BAEK) in external quality assurance using the reference method value concept, when applied in patient care. The allowed deviation of ±18% in external quality assessment (EQA) and ± 10% in internal quality control has been ultimately met by virtually all the different manufacturers and methods. However, such broad limits for permissible deviations are not suitable in view of medical requirements in patient care. The low-level acceptance criteria also depends on the previously used EQA materials used in Germany. In fact, HbA1c measurement results that are imprecisely measured or come from incorrectly calibrated devices are difficult to identify. With implementation of unprocessed fresh EDTA blood, the situation has changed. Until now systems with unit use reagents for point-of-care testing (POCT) of HbA1c are not mandatory to participate in EQA schemes in Germany. This paper outlines why there was a need to narrow the acceptance limits listed within the Rili-BAEK for HbA1c’s internal (to ± 3%) and external (to ± 8%) quality controls in EQA schemes for Germany, which will take place after a transition period in the next years. Higher quality in HbA1c measurements will help to avoid misdiagnosis of diabetes as well as potential over- or undertreatment of patients at risk for diabetes.
Keywords: HbA1c; quality control; external quality assessment scheme; sample material